A Systematic Examination of Teachers’ Optimism Based on Gender in A Diverse Educational Context - Islam, Md. Muzahid; Mimi, Afshana; Khatun, Murshida; Sarker, Pramath Chandra; Haque, Md. Nazmul (International Journal of Multi Discipline Science (IJ-MDS), 2025)
Optimism is a factor that evaluates variations in the extent to which individuals expect the future to be mostly fortunate. Additionally, it has a relationship with indicators of enhanced physical and mental health. This study evaluated the optimism levels of male and female teachers in distinct education settings, focusing particular attention on factors including gender, residence, and schooling level. The Revised Life Orientation Test (LOT-R) was utilised in the study as an instrument to evaluate teacher optimism. An equal number of teachers from primary and secondary schools, divided into gender-specific groups of 40, participated in this randomised sample study. Data were obtained using a questionnaire technique. MS Excel and GraphPad 8.0.1 were used to analyse the data. PAST edition 4.13 was utilised for creating the research's statistical figures within the context of the data evaluation process. The investigation's initial results demonstrated several notable patterns. First of all, male teachers were generally more optimistic than female teachers. Secondly, when it came to instructing in rural areas, male educators appeared more optimistic than female educators. Thirdly, male teachers were noticeably more optimistic in the field of their primary schooling. Lastly, there was a greater degree of optimism among male educators in the context of secondary school. This research would be a significant approach to promoting optimism in educational institutions and society by helping human development specialists understand how gender impacts optimism.